PEMBENTUKAN KARAKTER SISWA DI SEKOLAH DASAR MELALUI PENDIDIKAN SENI MUSIK - Siska Tresia Oktari; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe that the formation of student character can be formed through music art education carried out in elementary schools. This type of research uses a literature study. Data collection was carried out by seeking information from various journals, articles, books and magazines that are relevant to the title of the related article. Music arts education does not only function as the development of musical skills, but also has great potential in shaping the character of students. Music arts education provides opportunities for students to develop various aspects of positive character. Through music arts education, students can develop cooperation, discipline, perseverance, responsibility, creativity, and self-expression. Therefore, music education should be considered as an integral part of the elementary school curriculum, to provide valuable experience in character building.